Penggunaan Sistem Informasi Penelusuran Perkara (SIPP) di Pengadilan Negeri Boyolali Kelas 1B - Descy Aryani; Nala Nugid Juwita; Juan Masyura; Diva Ariesta Kusuma (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2022)
Sistem Informasi Penelusuran Perkara (SIPP) application developed by the Supreme Court is a form of implementing Information Disclosure in the Court. With the rapid development of technology and information, it has a significant impact, one of which is in the field of archiving carried out in the Court. This system contains a list of case files that can be used by all courts in Indonesia. This service is carried out using a participatory method where students participate in helping work in matters relating to the use of SIPP. In its implementation, it indirectly provides reliable information for the public as part of transparency in the court process, so as to increase public confidence in the court process and law in Indonesia.